Targeting Lewy body dementia with neflamapimod-rasagiline hybrids - Albertini, Claudia; Petralla, Sabrina; Massenzio, Francesca; Monti, Barbara; Rizzardi, Nicola; Bergamini, Christian; Uliassi, Elisa; Borges, Fernanda; Chavarria, Daniel; Fricker, Gert; Goettert, Marcia; Kronenberger, Thales; et al. (Archiv der Pharmazie, 2024)
Lewy body dementia (LBD) represents the second most common neurodegenerative dementia but is a quite underexplored therapeutic area. Nepflamapimod (1) is a brain-penetrant selective inhibitor of the alpha isoform of the mitogen-activated serine/threonine protein kinase (MAPK) p38α, recently repurposed for LBD due to its remarkable antineuroinflammatory properties. Neuroprotective propargylamines are another class of molecules with a therapeutical potential against LBD. Herein, we sought to combine the antineuroinflammatory core of 1 and the neuroprotective propargylamine moiety into a single molecule. Particularly, we inserted a propargylamine moiety in position 4 of the 2,6-dichlorophenyl ring of 1, generating neflamapimod-propargylamine hybrids 3 and 4. These hybrids were evaluated using several cell models, aiming to recapitulate the complexity of LBD pathology through different molecular mechanisms. The N-methyl-N-propargyl derivative 4 showed a nanomolar p38α-MAPK inhibitory activity (IC50 = 98.7 nM), which is only 2.6-fold lower compared to that of the parent compound 1, while displaying no hepato- and neurotoxicity up to 25 μM concentration. It also retained a similar immunomodulatory profile against the N9 microglial cell line. Gratifyingly, at 5 μM concentration, 4 demonstrated a neuroprotective effect against dexamethasone-induced reactive oxygen species production in neuronal cells that was higher than that of 1.
Zuerst veröffentlicht: 27. Februar 2024
Gesehen am 25.07.2024